The Degree Of Ambiguity Of Homonymous Syntactic Structures In The Bosnian Language - Hodžić, Jasmin (Slavica Lodziensia, 2017)
In this paper has been specifi cally considered the issue of the potential and the actual syntactic ambiguity (or syntactic homonymy) which has led to the results indicating that the existence of ambiguity in syntax is not negligible, and that the role of the context in the analysis of the syntactic ambiguity is not as it has been assumed. A selected number of examples have been presented to native speakers in order to assess the meaning. The results of this questionnaire show that the native speakers have confi rmed the ambiguity of all the sentences. Ambiguity has been additionally analyzed through the calculation of the degree of ambiguity (i.e., determination of the stability of meaning) and the index of the degree of ambiguity (i.e., determination of the consistency of meaning).